Sitobion miscanthi L type symbiont enhances the fitness and feeding behavior of the host grain aphid. Issue 4 (14th December 2022) - Li, Xinan; Sun, Yulin; Tian, Xujun; Wang, Chao; Li, Qian; Li, Qiuchi; Zhu, Saige; Lan, Chen; Zhang, Yunhui; Li, Xiangrui; Ding, Ruifeng; Zhu, Xun
Abstract: Background: Symbiotic bacteria affect physiology and ecology of insect hosts. The Sitobion miscanthi L type symbiont (SMLS) is a recently discovered and widely distributed secondary symbiont in the grain aphid Sitobion miscanthi Takahashi in China. Results: In this study, SMLS‐infected (SI) and SMLS‐uninfected (SU) aphid strains were obtained from field population. The artificially SMLS‐re‐infected (SRI) strain was established by injecting SU aphids with the SI strain hemolymph containing SMLS. The SRI and SU strains had identical genetic backgrounds and similar microbial community structures. Compared with the SU strain, adult longevity, survival rate, and fecundity were significantly greater in the SRI strain (biological fitness of 1.48). Moreover, the SRI strain spent more time ingesting phloem than the SU strain. A comparative transcriptome analysis indicated that reproduction‐ and longevity‐related genes were more highly expressed in the SRI strain than in the SU strain. Conclusion: The findings indicated that the infection with SMLS enhanced the Sitobion miscanthi fitness and feeding behavior. The beneficial effect of the SMLS on hosts could explain why it frequently infects the field populations in the grain aphid Sitobion miscanthi Takahashi in China. © 2022 Society of Chemical Industry. Abstract : The infection with Sitobion miscanthi L type symbiont (SMLS) enhanced the aphid adult longevity, survival rate and fecundity, and spent more time ingesting phloem.